2022
DOI: 10.1177/07308884221094539
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Discrimination in Hiring Before and During the COVID-19 Pandemic: Evidence from a Field Experiment of Accountants, 2018–2020

Abstract: In this article, we ask whether macro-level changes during the first year of the COVID-19 pandemic relate to changes in the levels of discrimination against women and Black job-seekers at the point of hire. We develop three main hypotheses: that discrimination against women and Black job-seekers increases due to a reduction in labor demand; that discrimination against women decreases due to the reduced supply of women employees and applicants; and that discrimination against Black job-seekers decreases due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
(136 reference statements)
1
10
0
Order By: Relevance
“…These results align with the subordinate male target hypothesis (Sidanius & Veniegas, 2000) and other studies that found that Black women were preferred over Black men (Hosoda, Stone, et al, 2003). This pattern is also supported by a recent study examining gender and racial discrimination before and after the pandemic (Chavez et al, 2022), which found that hiring outcomes for White and Black women equaled or exceeded those for White men, but Black men still struggled. This result highlights the importance of examining intersectionality as it may camouflage significant effects across demographic groups (Krings et al, 2022).…”
Section: Discussionsupporting
confidence: 62%
“…These results align with the subordinate male target hypothesis (Sidanius & Veniegas, 2000) and other studies that found that Black women were preferred over Black men (Hosoda, Stone, et al, 2003). This pattern is also supported by a recent study examining gender and racial discrimination before and after the pandemic (Chavez et al, 2022), which found that hiring outcomes for White and Black women equaled or exceeded those for White men, but Black men still struggled. This result highlights the importance of examining intersectionality as it may camouflage significant effects across demographic groups (Krings et al, 2022).…”
Section: Discussionsupporting
confidence: 62%
“…From the 44 articles examined, the literature highlights essential workers generally (19) and in specific industries: healthcare (8), agriculture (meat and farm workers) (5), service workers (1) [ 45 ], accounting (1) [ 49 ], and higher education (1) [ 70 ]. Most articles included multiple races (24), examining the work outcomes of White, Black, Hispanic, and sometimes, Indigenous and Asian adults.…”
Section: Resultsmentioning
confidence: 99%
“…The different findings for black workers for the samples excluding and including the post-COVID-19 months may be associated with compositional changes in the labor force that affected black workers during the COVID-19 pandemic. Recent research has shown that black workers were at a higher risk for being laid off (Dias 2021) and continued to experience discrimination in hiring during the post-COVID-19 recovery period (Chavez, Weisshaar, Cabello-Hutt 2022). For different reasons, the employment status of Hispanic and Asian workers was less affected in the post-COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%